Thermo-responsive nonionic amphiphilic copolymers as draw solutes in forward osmosis process for high-salinity water reclamation - Xu, Yilin (2022)
Recently, thermo-responsive nonionic amphiphilic copolymers have shown a great potential as forward osmosis (FO) draw solutes for high-salinity water desalination and zero-liquid discharge (ZLD). However, the relationship between the copolymer structural properties and key characteristics as draw solutes, as well as copolymer's chemical stability after regeneration have not been much studied. In this work, we systematically investigated poly (ethylene oxide)-block-poly (propylene oxide)-block-poly (ethylene oxide) (PEO-PPO-PEO) copolymers as draw solute. The results showed that the PEO segments significantly influenced the viscosity, osmotic pressure and lowest phase separation temperature of the copolymer aqueous solutions. Among four commercial copolymers studied, Pluronic® L35 with moderate molecular weight (Mn 1,900 Da), 50% PEO, and relatively high hydrophilic-lipophilic balance (HLB) showed the best draw solution (DS) performance. It also showed great stability in physiochemical properties and draw capacity after more than ten cycles of regeneration. On the other hand, despite the fact that membrane fouling was observed due to the use of copolymer DS, the FO flux (∼1.2 L m‒2 h‒1, as similar with the virgin membrane) was not affected when high-salinity feedwater such as seawater RO brine was applied. Overall, our study has provided a more comprehensive understanding on the characteristics of nonionic amphiphilic copolymer DS and showcased the promise of copolymer-driven FO process in high-salinity water desalination and ZLD.